Cytological features of mammary analogue secretory carcinoma of salivary gland: Fine‐needle aspiration of seven cases. Issue 10 (3rd March 2014) - Higuchi, Kayoko; Urano, Makoto; Takahashi, Reisuke H.; Oshiro, Hisashi; Matsubayashi, Jun; Nagai, Takeshi; Obikane, Hiyo; Shimojo, Hisashi; Nagao, Toshitaka
<x xml:space="preserve">Abstract</x> Mammary analogue secretory carcinoma (MASC) is a recently described salivary gland neoplasm that is defined by ETV6‐NTRK3 gene fusion. There have been few case reports on the cytopathologic features of MASC to date. We examined the clinicopathological and cytological features of seven cases of MASC defined by RT‐PCR analysis of the ETV6‐NTRK3 fusion gene. The cases occurred in three men and four women aged between 39 and 68 years, with a mean of 51.6 years. In five of these seven cases, the tumor involved the parotid gland. Histologically, all cases displayed predominantly microcystic patterns, often a mixture of follicular and papillary‐cystic structures. All tumors were immunoreactive for mammaglobin, S‐100 protein, and vimentin. Available fine‐needle aspiration cytology smears were cellular and exhibited many loosely cohesive syncytial clusters or isolated cells. Many histiocytes, some of which contained hemosiderin pigments, and variously shaped mucinous material were evident in the background or within the epithelial clusters. The majority of cases showed small to medium‐sized follicular structures with secreted materials. Papillary clusters were occasionally found. Tumor cells exhibited small to medium‐sized round to oval nuclei, with a smooth contour and indistinct or small nucleoli, and vacuolated cytoplasm. No tumor cells had obvious intracytoplasmic zymogen granules. It appeared that clusters of small to medium‐sized follicular and papillary configurations consisting of bland tumor cells with vacuolated cytoplasm, but lack of intracytoplasmic zymogen granules, in a mucinous or hemosiderin‐laden histiocyte‐rich background, were a characteristic cytological feature highly suggestive of MASC. Diagn. Cytopathol. 2014;42:846–855. © 2014 Wiley Periodicals, Inc.